The Liberty of the Italian City in the Late Middle Ages: Some Reflections (Edad Media. Revista de Historia, 2020)
The history of liberty in Italian cities of the late Middle Ages is confronted with a "great narrative" describing the political experience of cities with a communal tradition as an extraordinary experience of republican liberty, based on some solid assumptions: firstly, that the Communes had been a full expression of the citizens' liberty; secondly that factional struggle had led them into a crisis; and finally that lordly regimes had meant the end of liberty and paved the way for the foreign invasions of the late fifteenth century. The central paradigm of this "great narrative of liberty" is the identification of the political experience of Italian cities of communal tradition with the republican political system. However, this assumption seems to be a pre-understanding not supported by documentary evidence. A new research on libertates in late medieval Italian cities, freed from this enormous ideological burden, is required in order to understand the variety of meanings of the premodern concept of liberty, mainly focused on the claim of freedom as absence of dependence and/ or an arbitrary political regime. The methodological starting point is a return to the documentary sources in order to analyse the language used in them, a language which shows that the notion of liberty in Italian cities between the twelfth and fourteenth centuries takes a huge variety of meanings and declinations.
Keywords: City; Commune; Italy; Liberty; Republic; Republicanism